Value of vessel wall magnetic resonance imaging in the diagnosis of cerebrovascular diseases - Sherien Farag; Hany Zaki El-Dien; Yasser Abdelazeem; Mohammed Khaled Elewa; Khaled Abdelmaksoud; Ahmed ElSadek (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2020)
Abstract Background Intracranial vessel wall imaging can detect non-stenotic lesions with further characterization of stenotic lesions that have already been detected with common angiographic methods. Magnetic resonance imaging (MRI) of the intracranial vessel wall can describe the presence of both large and small atherosclerotic lesions and to characterize the lesions based on enhancement, plaque content, and vulnerability Objectives To assess suspicious lesions detected by magnetic resonance angiography for further evaluation by vessel wall MRI. Methods A total of sixteen ischemic stroke patients within 2 weeks from onset were recruited to this cross-sectional study. Magnetic resonance angiography was done to document intracranial arterial stenosis. Further high-field MR unit (3 Tesla MRI Scanner) was used to obtain vessel wall MR sequences (T1 pre-post contrast and T2 fat sat) to differentiate between intracranial atherosclerotic plaque, vasculitis, and moyamoya disease and to assess atherosclerotic plaque activity (vulnerability) Results Vessel wall MR imaging showed arterial wall thickening with irregular inner margin and eccentric enhancement in cases of intracranial atherosclerosis, where as in case of CNS vasculitis, it showed circumferential wall enhancement with regular smooth inner margin. In cases of moyamoya disease, the vessel wall MR showed a narrowing of the luminal artery without post-contrast enhancement of the wall, no hemorrhagic nor fatty content. Conclusion Vessel wall MR imaging is recommended for stroke patients with suspected intracranial large vessel atherosclerosis seen in MRA to assess atherosclerotic plaque activity and characterization of stenotic lesions